Production indices for dual purpose cattle in central Brazil - McManus,Concepta (2011)
This study examined the effects of crossbreeding low genetic potential cows of Bos indicus origin characterized by Gyr crossed with Holstein-Friesian and Simmental bulls to produce animals in a low input dual purpose system. The farm is situated near Brasilia, in the savannah region of Brazil. The climate of the region is classified as Aw by Köppen. Data was available on 1580 calvings and completed lactations of cows with three genetic types: Gyr, Holstein-Friesian × Gyr and Simmental × Gyr. The bulls ran with the cows all year round and the diet comprised of pasture (mainly Brachiaria and Andropogon) during the summer (rainy season) and milled sugar cane with added urea during the winter (dry season). A mineral salt mixture was available ad libitum. Data was analysed using Statistical Analysis System. The results show that, under low input management conditions, the crossbred cows produce approximately twice the volume of milk per lactation, calve at a younger age and have a shorter open period, but there are no significant differences between crosses for growth rates of the calves or body condition of the cows. In this system, crossbred cows had production higher indices than zebu cattle. The best indices were found for cows calving in the rainy season (September to December) and thinner cows (with body condition 3-5 on a scale of 9).